Analysis of The Effect of Durian Rind Texture on Sugar Content Using The Box-Counting Method - Arum Andary Ratri; Khoirul Umam; Devit Suwardiyanto; Junaedi Adi Prasetyo; Vivien Arief Wardhany (Universitas Nahdlatul Ulama Surabaya, 2023)
Durian is a popular fruit native to Southeast Asia, even labeled as the king of fruits. Currently, both fresh and processed durians have been very well received by the public in both local and export markets [1]. However, it is not uncommon for durians purchased in poor quality, such as bland taste, rotten, or immature [2]. Therefore, a method to identify the quality of durian is needed. One of the durian elements that can be used to identify its quality is the shape and texture of its outer skin. The object discussed in this paper is the relationship between the fractal dimensions of durian skin image and the sugar content of durian flesh. Its fractal dimensions are searched using the box-counting method. The box-counting method is used to calculate fractal dimensions with the fractal object placed in a box area. Then it is calculated by how many boxes are needed to cover all the fractal parts. The relationship was then analyzed using the coefficient of determination. The results of the analysis produce an R-Square value of 0,029333. The R-Square value obtained shows that the fractal dimension of the texture of the durian skin does not significantly affect the sugar content of the durian flesh.